A Multidisciplinary Approach in the Treatment of Tempromandibular Joint Pain Associated with Qat Chewing - Mansoor Shariff; Mohammed M. Al-Moaleem; Nasser M. Al-Ahmari (Hindawi Limited, 2013)
Pain of the tempro-mandibular joint (TMJ) has a direct bearing to missing teeth and excessive physical activity. Consumption of qat requires chewing on the leaves to extract their juice for long hours. A 65-year-old male Yemeni patient, a Qat chewer, reported to the university dental hospital at King Khalid University complaining of pain in left temporomandibular joint with missing mandibular anterior teeth. A multidisciplinary approach for the overall treatment of the patient was decided. Initial treatment was the relief of patient's pain with the help of a night guard. This was followed by a fabrication of anterior FPD. The case was under maintenance and follow-up protocol for a period of 8 months with no complaint of pain discomfort.